1993
DOI: 10.1007/bf00053149
|View full text |Cite
|
Sign up to set email alerts
|

Recent cohort trends in malignant melanoma by anatomic site in the United States

Abstract: The incidence of malignant melanoma has been increasing steadily in the United States. The increase may be due to lifestyle changes in subsequent generations or birth cohorts. The nine population-based tumor registries in the Surveillance, Epidemiology, and End Results program (SEER) have been in existence for a sufficient time to begin to investigate cohort trends for the US population. Cases were the 18,787 Caucasians aged 20 to 84 years, who reported to SEER registries with a diagnosis of melanoma in 1974-8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
25
0
3

Year Published

1995
1995
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 32 publications
3
25
0
3
Order By: Relevance
“…36 Our results are in agreement with several other studies showing that melanoma tends to occur most often on the trunk in white males and on the lower limb in white females. 18,20,[40][41][42][43][44][45][46] Gender differences in patterns of detection and knowledge regarding melanoma have been previously studied. This study, and others, show that women are more likely to discover their own lesions.…”
Section: Figurementioning
confidence: 99%
“…36 Our results are in agreement with several other studies showing that melanoma tends to occur most often on the trunk in white males and on the lower limb in white females. 18,20,[40][41][42][43][44][45][46] Gender differences in patterns of detection and knowledge regarding melanoma have been previously studied. This study, and others, show that women are more likely to discover their own lesions.…”
Section: Figurementioning
confidence: 99%
“…[1][2][3] Since the mid-1980s, however, the rates of increase began decreasing or at least leveling off. [4][5][6][7][8][9] Recent studies showed that the observed leveling-off in rates predominantly occurred in younger persons and the patterns showed positive effects for cohorts born after 1945 or 1950. 4,6,9 Conversely, the rate of increase in melanoma incidence and mortality has been significantly higher for age groups older than 60 years in Europe, the US, and Australia.…”
mentioning
confidence: 99%
“…Descriptive studies of malignant melanoma time trends have shown significant anatomic site and gender differences (Chen et al, 1994;Dennis et al, 1993;Thorn et al, 1990). These differences have generally been attributed to anatomic siteand gender-specific differences in time trends in patterns of sun exposure, a consequence of changes in clothing fashions and recreational habits.…”
mentioning
confidence: 99%